2020
DOI: 10.3390/cells9071692
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Metabolism in Cancer

Abstract: Peroxisomes are metabolic organelles involved in lipid metabolism and cellular redox balance. Peroxisomal function is central to fatty acid oxidation, ether phospholipid synthesis, bile acid synthesis, and reactive oxygen species homeostasis. Human disorders caused by genetic mutations in peroxisome genes have led to extensive studies on peroxisome biology. Peroxisomal defects are linked to metabolic dysregulation in diverse human diseases, such as neurodegeneration and age-related disorders, revealing the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 120 publications
(189 reference statements)
1
49
1
Order By: Relevance
“…Beyond its recognized role in metabolism and redox homeostasis, the peroxisome is now increasingly regarded as a signaling platform and a key organelle in cellular metabolic reprogramming with major consequences on the immune response, cell cycle, and cell differentiation [ 12 , 96 ]. Elegantly presented in the state of the art of Hlaváč and Souček, several studies have revealed a significant association between the level of expression of peroxisomal ABC transporters and various cancers [ 97 ].…”
Section: Human Diseasesmentioning
confidence: 99%
“…Beyond its recognized role in metabolism and redox homeostasis, the peroxisome is now increasingly regarded as a signaling platform and a key organelle in cellular metabolic reprogramming with major consequences on the immune response, cell cycle, and cell differentiation [ 12 , 96 ]. Elegantly presented in the state of the art of Hlaváč and Souček, several studies have revealed a significant association between the level of expression of peroxisomal ABC transporters and various cancers [ 97 ].…”
Section: Human Diseasesmentioning
confidence: 99%
“…However, the suppression of KHK is not dependent on HIF-2α-induced pexophagy, as recuse of the pexophagy by autophagy inhibition does not restore the expression of KHK [ 72 ]. Recent evidence has revealed that the levels of peroxisome proteins or enzymatic activities are either increased or reduced in various cancer types, suggesting that peroxisomes may have a tumor-promoting or tumor-suppressing function [ 73 , 74 ]. Understanding the mechanisms of pexophagy in the control of peroxisome homeostasis is of great importance to decipher the role of peroxisomes in carcinogenesis.…”
Section: Roles Of Pexophagy In Health and Diseasementioning
confidence: 99%
“…Interestingly, GLUT2 mRNA expression is increased following UGCG OE in NMuLi cells. It has been shown that GLUT2 (Tenen et al, 2021) and Acox1 (reviewed in (Kim, 2020)) are increased in HCC, which led us to hypothesize that this might be either a compensatory effect or an early-onset of pro-cancerous processes. PGC1α has an essential role in the control of hepatic gluconeogenesis (reviewed in (Liang and Ward, 2006)), which indicates that PGC1α is upregulated to allow for su cient energy supply for NMuLi/UGCG OE cells, which exhibit decreased OXPHOS and glycolysis.…”
Section: Expression Of Tumor Markers Affected By Ugcgmentioning
confidence: 99%